2016
DOI: 10.1063/1.4954666
|View full text |Cite
|
Sign up to set email alerts
|

Nano-crystallization in ZnO-doped In2O3 thin films via excimer laser annealing for thin-film transistors

Abstract: In a previous work, we reported the high field effect mobility of ZnO-doped In2O3 (IZO) thin film transistors (TFTs) irradiated by excimer laser annealing (ELA) [M. Fujii et al., Appl. Phys. Lett. 102, 122107 (2013)]. However, a deeper understanding of the effect of ELA on the IZO film characteristics based on crystallinity, carrier concentrations, and optical properties is needed to control localized carrier concentrations for fabricating self-aligned structures in the same oxide film and to adequately explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Further experiment can be conducted to fill empty space in Figure 3. In the binary system ZnO-In2O3 and In2O3-GeO2, just one binary compound cubic bixbyite was reported in perevious studies [7,8,19]. Electrical conductivity of reported ternary system as a function of In +3 content is given in Figure 4 and porosity corrections are made by the Bruggemann symmetric model [14].…”
Section: Resultsmentioning
confidence: 95%
“…Further experiment can be conducted to fill empty space in Figure 3. In the binary system ZnO-In2O3 and In2O3-GeO2, just one binary compound cubic bixbyite was reported in perevious studies [7,8,19]. Electrical conductivity of reported ternary system as a function of In +3 content is given in Figure 4 and porosity corrections are made by the Bruggemann symmetric model [14].…”
Section: Resultsmentioning
confidence: 95%
“…Doping can increase the electron concentration to improve the electrical characteristics and reliability of components [12]. Previous studies indicated that doping In 2 O 3 with another metal, such as ZnO, Zr, Al, and Ga [13]- [16], can enhance electrical properties and stability and be used in various semiconductor components.…”
Section: O 3 Exhibits High-mentioning
confidence: 99%
“…The most common strategy is performing a thermal annealing step > 400 °C for several hours to achieve acceptable device performance. ,, Attempts to lower the induced temperature on the device involve the use of microwave annealing, , high-pressure annealing, , and photochemical activation. In particular, photoactivation is a sustainable technique wherein the energetic photons from the light source aid in the decomposition of precursors and the subsequent densification of metal oxide. , Several reports have demonstrated UV irradiation to be effective in accelerating precursor decomposition and subsequent metal-oxide formation. , On the other hand, laser irradiation is another strategy that is preferred over conventional thermal treatment in terms of addressing issues such as high thermal budget, long processing times, and incompatibility with heat-sensitive substrates, which leads to mechanical failure . Laser processing primarily works by generating high energy in a confined area using a focused laser to induce photothermal effects at a target location. This localization of the thermal effect makes it possible to produce minimal to zero interactions with the underlying layers, substrate, or even adjacent structures, making it interesting in diverse materials processing, which requires selective annealing, patterning, crystal growth, , and ablation. , Laser irradiation has been used to tailor the characteristics of metal oxide films and nanostructures for diverse applications such as dielectric materials, , solar cells, ferroelectric oxide thin films, transparent conductors, , and TFTs. ,,,, Previously, we demonstrated the use of excimer laser and UV irradiation to induce structural modification in an a-IZO film . Combining excimer laser irradiation with UV irradiation has been shown to be critical for achieving the superior characteristics of fully solution-processed a-IZO TFTs.…”
Section: Introductionmentioning
confidence: 99%
“…26 Laser processing primarily works by generating high energy in a confined area using a focused laser to induce photothermal effects at a target location. 26−28 This localization of the thermal effect makes it possible to produce minimal to zero interactions with the underlying layers, substrate, or even adjacent structures, 26 making it interesting in diverse materials processing, which requires selective annealing, 29−32 patterning, 33−35 crystal growth, 36,37 and ablation. 33,38 Laser irradiation has been used to tailor the characteristics of metal oxide films and nanostructures for diverse applications such as dielectric materials, 31,39 solar cells, 40 ferroelectric oxide thin films, 41 transparent conductors, 32,42−44 and TFTs.…”
Section: ■ Introductionmentioning
confidence: 99%